Heterochrony, dental ontogenetic diversity, and the circumvention of constraints in marsupial mammals and extinct relatives - Forasiepi, Analia Marta (2014)
In marsupial mammals and their extinct relatives-collectively, metatherians-only the last premolar is replaced, but the timing of dental eruption is variable within the group. Our knowledge of fossils metatherians is limited, but is critical to understanding several aspects of the evolution and morphological diversification of this clade. We analyzed the sequence of eruption of 76 specimens of metatherians, including Sparassodonta, an extinct clade of specialized carnivores from South America. In Sparassodonta (1) the P3/p3 erupt simultaneously, in common with some didelphids (in other didelphids, p3 erupts before P3, whereas in the remaining didelphids, some peramelids, one caenolestid, and Pucadelphys this order is reversed); (2) the upper and lower molars at the same locus erupt more in synchrony than in other carnivorous metatherians in which the lower molars clearly precede the upper equivalents; (3) the upper canine in thylacosmilids and proborhyaenids is hypselodont; (4) species with similar molar morphologies have different morphologies of the deciduous premolars, suggesting diverse diets among the juveniles of different taxa; (5) deciduous teeth are functional for a long period of time, with thylacosmilids even retaining a functional DP3 in the permanent dentition. The retention of the DP3 and the hypertrophied and hypselodont upper canine of thylacosmilids represent clear heterochronic shifts. Specializations in the timing of dental eruption and in the deciduous tooth shape of sparassodonts are evolutionary mechanisms that circumvent constraints imposed by the metatherian replacement pattern and increase morphological disparity during ontogeny.